Introduction of Ammonites from the Dalichai Formation in Polour Section Central Alborz, Iran - Sohrabi Mollayousefi, Masoomeh; Kiarostami, Kiana (Indonesian Journal of Earth Sciences, 2025)
The studies done on Dalichai Formation in Central Alborz, South Polour Formation of an 80 m thick that are systematically sampled at intervals of 2 meters and selected the 40 rock samples for the preparation of thin sections considered and in addition to lithology; characteristics of the stone, and index examples of Ammonites were also studied. Dalichai formation lithology in the study area is rich in terms of alternating gray sandstone and marl with Ammonites Fauna. Based on the study of fossil fauna, the oldest identified ammonite in the studied section is Procerites (Early Bathonian), and the youngest is Reineckeia sp. (Late Callovian). The distribution of ammonites indicates that the eastern Alborz region had marine connections with northwestern Europe and the Mediterranean marginal areas during the Middle Jurassic period, and the study area was located north of the Tethys Ocean. Based on its stratigraphic position of the middle Jurassic Age Formation, Dalichai Ammonites with peer review study sections and microfossils Bathonian-Callovian age Dalichai is accurate. Lar Formation covers this formation with a gradual contact and has been parallel to the Shemshak Formation on an erosional unconformity. Through the examination of stratigraphy and the correlation of formations in the studied sequence, it was determined that the lower part of the Dalichai Formation is equivalent to other formations in Iran, including the Parvdeh Formation in the Shotori Mountains, the Kashfrood Formation in the Kopeh Dagh, and the lower part of the Baghamshah Formation in the Tabas Basin. The variations in thickness of the Dalichai Formation in the eastern Alborz region indicate relative subsidence of the sedimentary basin, a delay in sea-level rise, and the exit of sediments from seawater. These changes are indicative of the Middle Cimmerian tectonic event, which is observed as an erosional unconformity at the lower boundary of the Dalichai Formation.